2006
DOI: 10.1002/hed.20455
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of small reconstruction plates in vascularized bone graft mandibular reconstruction

Abstract: Use of the smaller 2.0-mm LRP was not associated with an increase in the complications of plate fracture, exposure, infection, or nonunion. Because of its lower profile and ease of application, the 2.0-mm LRP is our plate of choice for mandibular reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 24 publications
3
31
0
6
Order By: Relevance
“…The four main flap donor sites were the fibula with 6178 flaps (8, 12, 16-18, 20-22, 24, 26-28, 32-55, 57-59, 61-64, 66-, 79, 81-83, 85, 87-89, 93, 94, 96-104, 106, 108 -131, 131, 133, 135, 137-141, 143, 145-154, 156, 158-169, 171-175, 179-184, 186-193, 195, 196, 198-200, 202-207, 209, 210, 212-216, 218-223, and 225-229), the iliac crest with 1380 flaps (8, 12-15, 17-20, 26, 29,31, 36, 38, 41, 45, 48, 50, 53, 54, 57-60, 62, 63, 65, 67, 72, 74, 75, 77, 79, 83, 84, 86, 87, 92, 96, 98, 99, 102, 105, 112-115, 121, 132, 149, 151, 152, 155, 157, 158, 161, 168, 170, 171, 173, 174, 177, 178, 181, 183, 186, 201, 211, 212, 216, 219, 227), composite radius with 1127 flaps (8, 10-12, 17, 20, 23, 25, 30, 32, 33, 48, 50, 56, 62, 67, 72, 75, 77, 80, 85, 87, 91, 93, 95, 96, 98, 99, 104, 113, 114, 133, 150, 152 154, 165, 176, 180, 183, 185, 203, 213, and scapula with 709 flaps (8,9,12,14,17,26,32,45,46,48,50,53,58,59,63,67,70,74,77,85,87,90,93,96,99,113,114,134,136,142,144,151,156,169,172,189,191,194,…”
Section: Flap Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four main flap donor sites were the fibula with 6178 flaps (8, 12, 16-18, 20-22, 24, 26-28, 32-55, 57-59, 61-64, 66-, 79, 81-83, 85, 87-89, 93, 94, 96-104, 106, 108 -131, 131, 133, 135, 137-141, 143, 145-154, 156, 158-169, 171-175, 179-184, 186-193, 195, 196, 198-200, 202-207, 209, 210, 212-216, 218-223, and 225-229), the iliac crest with 1380 flaps (8, 12-15, 17-20, 26, 29,31, 36, 38, 41, 45, 48, 50, 53, 54, 57-60, 62, 63, 65, 67, 72, 74, 75, 77, 79, 83, 84, 86, 87, 92, 96, 98, 99, 102, 105, 112-115, 121, 132, 149, 151, 152, 155, 157, 158, 161, 168, 170, 171, 173, 174, 177, 178, 181, 183, 186, 201, 211, 212, 216, 219, 227), composite radius with 1127 flaps (8, 10-12, 17, 20, 23, 25, 30, 32, 33, 48, 50, 56, 62, 67, 72, 75, 77, 80, 85, 87, 91, 93, 95, 96, 98, 99, 104, 113, 114, 133, 150, 152 154, 165, 176, 180, 183, 185, 203, 213, and scapula with 709 flaps (8,9,12,14,17,26,32,45,46,48,50,53,58,59,63,67,70,74,77,85,87,90,93,96,99,113,114,134,136,142,144,151,156,169,172,189,191,194,…”
Section: Flap Optionsmentioning
confidence: 99%
“…On the other hand, there were only five papers (99,114,154,180,183) in which the type of flap could not be related to non-union.…”
Section: Non-unionmentioning
confidence: 99%
“…The mandibular reconstruction system used in our series and in the series reported by Farwell et al 9 are the 2 most commonly used mandibular reconstruction systems in the United States, having roughly equal market shares and together accounting for about 70% of all cases. Unlike the low-profile plates used by Farwell et al, 9 all reconstructions in our series were carried out using an LRMP with a relatively high profile height of 2.8 mm. The plating system used in our series (Leibinger Universal Mandibular System, StrykerCraniomaxillofacial) also includes a low-profile LMRP with a profile height of 1.5 mm.…”
Section: Commentmentioning
confidence: 99%
“…22 Large clinical series that explored the association of radiation therapy with free flap complication rates reached different conclusions. 4,8,9,17,23,24 Choi et al, 23 in a study of 100 consecutive patients undergoing fibula free flap reconstruction of the mandible, did not find that radiation therapy was associated with an increase in complication rates. Conversely, in a similar study of 140 patients undergoing fibula free flap mandible reconstruction, Deutsch et al 24 found that administration of radiation therapy increased complication rates regardless of the timing of the dose.…”
Section: Commentmentioning
confidence: 99%
“…Locking screw plate designs are preferred to compensate for the latitude in contouring which may be somewhat less precise and also the need for less compressive clamping of the plate to the periosteal blood supply of the neomandible. [25][26][27] Plates should be placed transperiosteally and screw holes should be drilled monocortically into the flap. Screws on the native side i.e., on the residual original mandible should be placed bicortically and may be subperiosteal with limited dissection advisable.…”
Section: Refinements and Nuances -Fibula Microvascular Free Flap Ostementioning
confidence: 99%